ENZYME PRODUCTION ABILITY BY BACILLUS SUBTILIS AND BACILLUS LICHENIFORMIS - A COMPARATIVE STUDY - Vijayalakshmi, S; Ranjitha, J; Rajeswari, V Devi (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: B.subtilis and B.licheniformis have been reported as one of the potential protease producer. Hence, an attempt has been made to optimize and compare the enzyme production by entrapment and fermentor conditions. Methods: Growth profile of both the strains has been studied. Optimization of culture conditions with respect to pH, temperature, agitation, carbon, nitrogen sources and metals has also been analyzed. Immobilization studies have been conducted for the strains. Enzyme production ability in fermentor has been premeditated. Results: Growth profile for both the strains was found to be similar. Strains were optimized for maximal enzyme production. Fermentation has yielded higher production of enzyme (8080 U/ml) compared to immobilization (850 U/ml). Conclusion: B.subtilis was more stable in enzyme production with immobilization and fermentation when compared to B.licheniformis. Keywords: B.subtilis, B.licheniformis, Immobilization, Fermentation